Modeling Cointegrated Nonstationary Air Pollution Data: A Forecasting Study of NO₂ and SO₂ in Indonesia (1950–2022) - Adnan, Arisman; Erda, Gustriza; Wamiliana; Russel, Edwin (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Air pollution from nitrogen dioxide (NO2) and sulfur dioxide (SO2) poses serious threats to human respiratory health and contributes to environmental degradation through acid rain formation. In Indonesia, despite rapid industrialization and increasing emissions, studies examining the interrelated dynamics between NO2 and SO2 at the national level remain limited, with most research focusing only on provincial areas and short time periods. This study fills this gap by analyzing the dynamic relationship between NO2 and SO2 using comprehensive national-level time series data from 1950 to 2022. The analysis examines short-term adjustments, long-term equilibrium patterns, directional causality, and shock responses between the two pollutants. The analysis focuses on identifying the best statistical model to capture the interaction between the two variables. Granger causality tests, impulse response functions (IRFs), and forecast error variance decomposition are applied to examine causal links and response dynamics. The data exhibits nonstationary but cointegrated with rank r=1, indicating a long-run equilibrium correlation between two pollutants. Consequently, the Vector Error Correction Model, VECM(4), is selected as the most appropriate model. The study also provides 10-year forecasts for both pollutants insights into potential future air pollution trends in Indonesia, with NO2 rising from 5.29 to 8.09 million tons and SO2 from3.38 to 5.10 million tons, underscoring the urgent need for integrated emission control policies that address both pollutants simultaneously rather than in isolation.